2021
DOI: 10.5213/inj.2142168.084
|View full text |Cite
|
Sign up to set email alerts
|

Polydeoxyribonucleotide Attenuates Airway Inflammation Through A2AR Signaling Pathway in PM10-Exposed Mice

Abstract: Purpose: Inhalation of air containing high amounts of particular matter (PM) causes various respiratory disorders including asthma, chronic obstructive pulmonary disease, and lung cancer. The changes of expression of inflammatory factors by polydeoxyribonucleotide (PDRN) administration in the PM10-exposed trachea inflammation model were evaluated.Methods: PM<sub>10</sub> was administered to mouse trachea to induce acute inflammatory damage, and changes in inflammatory factors were observed after ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…On the other hand, some pro‐inflammatory agents (IL‐8, TNF‐α, IL‐6, IL‐17, IL‐1β, and ICAM‐1) were found to be modulated by EP3 in this research. As we know, CREB could mediate the pro‐inflammatory cytokines 43,44 . Thus, it can be concluded that EP3 promoted the inflammatory responses through up‐regulation of CREB.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, some pro‐inflammatory agents (IL‐8, TNF‐α, IL‐6, IL‐17, IL‐1β, and ICAM‐1) were found to be modulated by EP3 in this research. As we know, CREB could mediate the pro‐inflammatory cytokines 43,44 . Thus, it can be concluded that EP3 promoted the inflammatory responses through up‐regulation of CREB.…”
Section: Discussionmentioning
confidence: 93%
“…As we know, CREB could mediate the pro‐inflammatory cytokines. 43 , 44 Thus, it can be concluded that EP3 promoted the inflammatory responses through up‐regulation of CREB.…”
Section: Discussionmentioning
confidence: 99%
“…Previous papers have demonstrated that adenosine A 2Ar activation prevents ROS generation, also reducing inflammation and the apoptotic process [24,25]. PDRN, which is recognized as an A 2Ar agonist, showed several properties-including antioxidant, anti-apoptotic and anti-inflammatory ones-in several pre-clinical in vivo disease models, such as airway inflammation, cerebral ischemia, interstitial cystitis, acute lung injury, and ischemic colitis [26][27][28][29][30]. Moreover, a previous clinical trial demonstrated that PDRN eye drops stimulated corneal epithelium regeneration, thus supporting the hypothesis that it could be used for the treatment of corneal diseases [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…28 Intracellular cAMP levels are regulated by the state of adenosine bound to A 2A R. 29 PKA activation and PKA-mediated protein phosphorylation by cAMP form the cAMP−PKA signaling pathway, which further inhibits the activation of the NF-κB pathway. 30,31 Zuo et al found that, following the activation of the sympathetic nervous system in rats after stroke, adrenaline activated the expression of cAMP, PKA levels increased, and the NF-κB pathway was inhibited. 32…”
Section: Iap Signal Transductionmentioning
confidence: 99%